New species, corallivory, in situ video observations and overview of the Goniasteridae (Valvatida, Asteroidea) in the Hawaiian Region - Mah, Christopher L. (Zootaxa, 2015)
Two new species of Goniasteridae, Astroceramus eldredgei n. sp. and Apollonaster kelleyi n. sp. are described from the Hawaiian Islands region. Prior to this occurrence, Apollonaster was known only from the North Atlantic. The Goniasteridae is the most diverse family of asteroids in the Hawaiian region. Additional in situ observations of several goniasterid species, including A. eldredgei n. sp. are reported. These observations extend documentation of deep-sea corallivory among goniasterid asteroids. New species occurrences presented herein suggested further biogeographic affinities between tropical Pacific and Atlantic goniasterid faunas.